Wasilah al Lu’bah al Lughowiyah Broken Square wa Snow Balling fii Ta’lim al Lughoh al ‘Arabiyyah li Tarqiyah Maharoh al Qiroah - In'ami, Moh; Shara, Putri Zunita (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2018)
مستخلص البحثالمدرسة الثانوية الإسلامية منبع الأعلى فوروادادي كروبوكان هي المدرسة فيها تعلم اللغة العربية. اما اهداف هذا البحث فهو لأن يعرف فعالية وسيلة اللعبة اللغوية  "بروكون سقوار" (Broken Square) و"سنو بوليج" (Snow Balling) في تعليم اللغة العربية لترقية مهارة القراءة في الفصل  العاشر بالمدرسة الثانوية الإسلامية منبع الأعلى. ومنهج هذا البحث هو " منهج كمي" (quantitative) ونوع هذا البحث "بحث تجريبيّ"، بشكل التصميم Pretest-Posttest Group Design . نتائج من درجة اختبار "ت" العلاقة   هي 4،66   1،992 من مستوى دلالة 5%. وخلاصة البحث، أن موجدة فعالية تطبيق وسيلة اللعبة اللغوية "بروكون سقوار" (Broken Square) و"سنو بوليج" (Snow Balling) في تعليم اللغة العربية لترقية مهارة القراءة في الفصل العاشر بالمدرسة الثانوية الإسلامية منبع الأعلى فوروادادي كروبوكان. والفرضية في هذا البحث مقبولة.الكلمات المفتاحية: وسيلة اللعبة اللغوية، "بروكون سقوار" (Broken Square)، "سنو بوليج" (Snow AbstrakAliyah Madrasah Manbaul Alaa Purwodadi Grobogan is one of the Madrasas that teaches Arabic. The purpose of this study was to determine the effectiveness of the application of Broken Square and Snow Balling language game media in learning Arabic in class X Madrasah Aliyah Manbaul Alaa. The approach of this research is a quantitative approach to experiment with the Pretest-Posttest Group Design design. In this study researchers collected data using test, observation and documentation methods. Experimental research is very important as a method made to find out the results of the reality of cause and effect. On this occasion, the researcher intends to find out the level of reading skills of students in class X Aliyah Madrasah Manbaul Alaa using Broken Square and Snow Balling language games, by comparing the control class and the experimental class. From this study, the results of the T.test correlation were 4.66 ˃ which is 1.992 at a significance level of 5%. Then it can be said that the language of Broken Square and Snow Balling is effective in learning Arabic to improve reading skills in class X Manbaul Aliyah Madrasah Alaa Purwodadi Grobogan. So, the hypothesis in this study was accepted.Keywords: Language Game Media, Snow Balling, Broken SquareKata Kunci: Media Permainan Bahasa, Snow Balling, Broken Square